To Enhance the RPS Game using Open CV & CV Zone by using Python Platform - Sabharwal, Harshdeep Singh; Majumdar, Tushar Kanti; Saroop, Shashank; Meena, Lokesh (International Journal of Computer Sciences and Engineering, 2023)
The paper involves the development of a rock- paper-scissors game using computer vision techniques, specifically gesture recognition. The game aims to provide an engaging and interactive user experience by allowing players to use hand gestures to play the game against a computer opponent. The user interface was designed for optimal user experience, incorporating visual feedback to effectively engage the player. The accuracy of gesture recognition was evaluated using quantitative metrics, measuring the precision of identifying rock, paper, and scissor gestures. The paper serves as an educational tool to demonstrate the practical applications of computer vision in gaming scenarios, potentially inspiring interest in STEM fields. It sets the foundation for future advancements in computer vision applications, with potential enhancements including multi- player functionality, improved gesture recognition using deep learning models, and integration into augmented or virtual reality environments. While the rock-paper-scissors game using OpenCV and CV Zone has several merits, there are also a few demerits to consider, indicating areas for further improvement. Overall, the paper contributes to the practical understanding of gesture recognition and image processing within the context of an interactive gaming application.